A rambler steals home - Higgins, Carter (Houghton Mifflin Harcourt, 2017)
Derby, Garland, and Triple Clark usually spend each season traveling highways in their Rambler, but when small-town Ridge Creek calls them back to Virginia one summer, everything changes. Selling burgers and fries out of Garland's Grill after each baseball game, Derby forms summer traditions that make her feel more at home than ever before. But when someone in town needs Derby's help, she discovers deeply held stories and secrets that could change her mind.